The role of behavioral bias on financial decision making: a systematic literature review and future research agenda - Umu Rosyidah; Heri Pratikto (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2022)
Purpose — This paper aims to analyze current research trends, identify theoretical perspectives, and identify research topics of behavioral bias in financial decision-making in the future.Research method — To perform bibliometric analysis, this article uses a systematic literature review, as well as content analysis. This article uses a total of 51 publications between 2018 and 2022 as the sample for the literature review, directed by PRISMA. The tool used in analyzing bibliometrics is VOSviewer. Meanwhile, content analysis is conducted to build theoretical perspectives and proposed future research agendas.Result — This systematic review explains the number of articles per year, most influential articles, leading journals, leading countries, leading authors, important keywords, and research cluster networks. Besides, this article also discovers seven behavioral biases that can be analyzed to gain a theoretical perspective on behavioral bias. The seven behavioral biases are Heuristic Bias, Self-Attribution Bias, Framing Bias, Herding Bias, Aversion Bias, Disposition Effect, and Overconfidence Bias,. In the scientific mapping analysis, important keywords are obtained, and the author's research cluster network is to discover topics that rarely researched to be offered in future research.Recommendation/significance/contribution — In contrast to previous studies of behavioral bias, which were dominated by survey-based research, this paper provides a different reference by using a systematic literature review method that provides coverage of the main research issues and theoretical arguments about behavioral bias in financial decisions. In addition, this paper offers new ideas about potential research fields by identifying studies in developing countries that are still rarely carried out compared to developed countries.